The regulation of multinational companies in subsaharian Africa : From instrumentalization to the consideration of sustenable collective development through CRS (Corporate Social responsability) strategies - (:unkn) unknown (My University, 2022)
Due to its regulatory power, Corporate Social Responsibility (CSR) is fundamentally an instrument at the service of sustainable development. Thus, the emergence and dissemination of this instrument in sub-Saharan Africa must meet several needs, first and foremost the achievement of the Sustainable Development Goals (SDGs) and the contribution to the achievement of the Millennium Development Goals (MDGs). It is in this perspective that multinational companies find their place and are targeted by the normative field of CSR. The ethical and social questioning of multinational companies in sub-Saharan Africa inevitably leads to the search for different regulatory levers under the three (3) aspects, namely environmental, social and economic, for the operational implementation of CSR. Without obscuring the proliferation of CSR initiatives, including the voluntary approaches of multinational companies often materialized by codes of conduct, a binding regulatory system seems to be taking shape on an international scale under the impetus of international organizations, pressure from NGOs and stakeholders including investors. Consequently, multinational companies, anxious to preserve their image, their legitimacy as well as their anchoring in the territories where they are located, must guarantee the transparency and consistency of practices, faced with the lack of effectiveness often observed in CSR discourse which does not respond only to marketing and commercial purposes. This instrumentalization justifies the interference of the law and the progressive construction of a real CSR law, with an approach that is both regulatory and tends to favor the production of binding standards, at least exempt from any instrumentalization and strategic by providing a competitive advantage to companies committed to CSR through responsible consumption and so that they contribute to the sustainable collective development of the regions where they operate.
Keywords: African Research